Study on parental involvement in Vietnamese primary students’ learning: insights from the era of educational reform - Hanh Van, Thi Hong; Tran, Xuan Quang; Vy Nguyen, Thi Phuong; Le, Thai Hung (International Journal of Evaluation and Research in Education (IJERE), 2025)
In light of Vietnam’s recent educational reforms emphasizing competency-based learning, this research explores how Vietnamese parents engage in their children’s education and the relationship between this involvement and students’ academic performance. Employing both quantitative (surveys) and qualitative (interviews) methods, the study focuses on three critical aspects of parenting and the family environment, based on Epstein’s theory: communication between parents and teachers, volunteering, and collaboration with the community. Quantitative data, analyzed using SPSS software, revealed the frequency of parental involvement activities, providing a comprehensive picture of both common and less frequent activities. Pearson correlation results confirmed a positive relationship between active parental involvement and student performance. The qualitative findings further highlight the challenges parents face when engaging in their children’s education and offer suggestions for improving parental participation. Overall, the paper provides valuable insights into the dynamics of parental involvement in Vietnamese schools and proposes practical, contextually appropriate solutions to enhance educational quality by strengthening cooperation between schools and parents.